Barrier enclosure in tracheostomy: a protective box for healthcare workers during the coronavirus disease 2019 pandemic. Issue 3 (20th March 2022) - Nair, N P; Sharma, V; Dixit, A; Goyal, S; Dixit, S G; Goyal, A; Misra, S
Abstract: Background: Tracheostomy, being a high aerosol-generating procedure, poses a great challenge to surgeons, especially during the coronavirus disease 2019 pandemic. It is important to preserve staff numbers as this fight may go on for a long time. Personal protective equipment plays a key role in the protection of healthcare workers. Barrier enclosure has been attempted in procedures such as intubation and tracheostomy. The use of boxes became popularised for intubation and they have been utilised in many centres. Methods: This paper describes the box designed by our team and presents our surgical experience with the box. The box is made of transparent acrylic. It is sealed at all ends, with a negative-pressure environment. The hand ports were designed to allow maximum manoeuvrability for surgeons, without restricting hand movements. Conclusion: The proposed box will provide more protection to healthcare workers during tracheostomy. However, the box is yet to be validated.